Features of deforming of composite inductors during electromagnetic processing of materials - Lavinsky, D. V.; Anischenko, G. O.; Konokhov, V. I. (Одеський національний морський університет, 2023)
The article proposes an effective method of analyzing the elastic-plastic deformation of composite structures under the influence of an electromagnetic field. The general mathematical formulation of the coupled problem of the deformation of conductive bodies in the presence of an electromagnetic field is considered. To construct a numerical solution method, the initial problem is reduced to finding the minimum of the total energy of the system. The finite element method is used as a numerical solution method. The proposed method is applied to the analysis of the deformation of the "inductor-workpiece" system of the technological operation of magnetic pulse processing of metals. Conclusions. Some results are presented that allow making certain recommendations regarding the design and application of technological operations of a similar class.

У статті запропоновано ефективний метод аналізу пружно-пластичного деформування складених конструкцій під дією електромагнітного поля. Розглянуто загальну математичну постановку зв’язаної задачі деформування електропровідних тіл при наявності електромагнітного поля. Для побудови методу чисельного розв’язку вихідна задача зведена до пошуку мінімуму повної енергії системи. В якості чисельного методу розв’язання використовується метод скінчених елементів. Запропонований метод застосований для аналізу деформування системи „індуктор–заготовка” технологічної операції магнітно-імпульсної обробки металів. Висновки. Представлені деякі результати, які дозволяють робити певні рекомендації щодо проектування та застосування технологічних операцій подібного класу.
Особливості деформування складених індукторів при електромагнітній обробці матеріалів
Keywords: non-stationary deformation; electromagnetic field; finite element method; magnetic-pulse processing; пружно-пластичне деформування; електромагнітне поле; метод скінчених елементів; магнітно-імпульсна обробка